N-P Fertilization Inhibits Growth of Root Hemiparasite Pedicularis kansuensis in Natural Grassland - Liu, Yanyan; Taxipulati, Teyibai; Gong, Yanming; Sui, Xiaolin; Wang, Xuezhao; Parent, Serge-Étienne; Hu, Yukun; Guan, Kaiyun; Li, Airong (Frontiers in Plant Science, 2017)
Fertilization has been shown to affect interactions between root hemiparasitic plants and their host plants, alleviating damage to the hosts by parasitism. However, as a majority of studies were conducted in pot cultivation, the influence of fertilizer application on root hemiparasites and the surrounding plant community in field conditions as well as relevant mechanisms remain unclear. We manipulated soil nutrient resources in a semi-arid subalpine grassland in the Tianshan Mountains, northwestern China, to explore the links between fertilization and plant community composition, productivity, survival, and growth of a weedy root hemiparasite (Pedicularis kansuensis). Nitrogen (at a low rate, LN, 30 kg N ha-1 yr-1 as urea; or at a high rate, HN, 90 kg N ha-1 yr-1 as urea) and phosphorus (100 kg ha-1 yr-1 as Ca(H2PO4)2•H2O) were added during two growing seasons. Patterns of foliar nutrient balances were described with isometric log ratios for the different plant functional groups receiving these fertilization regimes. Fertilization with LN, HN and P reduced above-ground biomass of P. kansuensis, with above-ground biomass in the fertilization treatments respectively 12%, 1% and 39% of the value found in the unfertilized control. Up to 3 times more above-ground biomass was produced in graminoids receiving fertilizers, whereas forb above-ground biomass was virtually unchanged by the fertilization regimes and forb species richness was reduced by 52% in the HN treatment. Fertilization altered foliar nutrient balances, and distinct patterns emerged for each plant functional group. Foliar [C | P,N] balance in the plant community was negatively correlated with above-ground biomass (P=0.03). The inhibited competitiveness of P. kansuensis, which showed a much higher [C | P,N] balance, could be attributed to reduced C assimilation rather than mineral nutrient acquisition, as shown by significant increase in foliar N and P concentrations but little increase in C concentration following fertilization.